2014
DOI: 10.1007/s00267-014-0405-9
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Common Patterns in Diverse Systems: Effects of Exurban Development on Birds of the Adirondack Park and the Greater Yellowstone Ecosystem, USA

Abstract: We examined the impacts of exurban development on bird communities in Essex County, New York and Madison County, Montana by comparing differences in abundance of songbirds between subdivisions and control sites in both regions. We hypothesized that impacts to bird communities would be greater in the relatively homogeneous, closed canopy Adirondack forest of northern New York State than they would be in the more naturally heterogeneous grasslands interspersed with trees and shrubs of the Greater Yellowstone Eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Exurban homes in the Adirondacks have been shown to cause significant shifts in bird community structure, usually with generalist and edge species increasing in abundance at the expense of more sensitive, forest interior species (Glennon and Kretser 2013;Glennon et al 2014). Similar responses of bird communities to exurban housing development have been observed in California (Merenlender et al 2009), Montana (Glennon et al 2014), New England (Kluza et al 2000), the mid-Atlantic (Suarez-Rubio et al 2013), and elsewhere across the United States (Wood et al 2014). However, while many species are displaced by the construction of a new home, some species that are typically considered to be sensitive to forest fragmentation and anthropogenic disturbance-such as our model organism, the ovenbird (Porneluzi et al 2011)-will often remain in the wake of the development and continue to inhabit the area (Kluza et al 2000;Glennon and Kretser 2013).…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Exurban homes in the Adirondacks have been shown to cause significant shifts in bird community structure, usually with generalist and edge species increasing in abundance at the expense of more sensitive, forest interior species (Glennon and Kretser 2013;Glennon et al 2014). Similar responses of bird communities to exurban housing development have been observed in California (Merenlender et al 2009), Montana (Glennon et al 2014), New England (Kluza et al 2000), the mid-Atlantic (Suarez-Rubio et al 2013), and elsewhere across the United States (Wood et al 2014). However, while many species are displaced by the construction of a new home, some species that are typically considered to be sensitive to forest fragmentation and anthropogenic disturbance-such as our model organism, the ovenbird (Porneluzi et al 2011)-will often remain in the wake of the development and continue to inhabit the area (Kluza et al 2000;Glennon and Kretser 2013).…”
Section: Introductionmentioning
confidence: 80%
“…The houses around which we captured ovenbirds are located within five areas zoned for low-density residential subdivision, and we treated each house as an independent unit because of the large degree of variation in parcel size, house size, lawn size (and other measures of landscaping intensity), levels of human activity (e.g., full-time vs. part-time residents), and other characteristics among properties. For comparison to ovenbirds nesting near houses, we captured ovenbirds at six reference areas also used by Glennon and Kretser (2013) and Glennon et al (2014) that are undeveloped, have low levels of human activity, and are protected as New York State Forest Preserve lands. Reference areas were chosen by identifying the closest areas of accessible undeveloped land of the same habitat type as the housing sites and of sufficient size to contain interior forest far from houses and roads.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…George and Dobkin [44] suggested that avian populations in parts of the Western US have contended with natural heterogeneity for thousands of years and may be less affected by fragmentation processes such as exurban development than avian populations of the relatively more homogeneous landscapes of the pre-European-settlement Eastern US. We previously examined changes in breeding bird community structure in exurban subdivisions and control areas between the Adirondack Park in northern NY and the Madison Valley, MT of the Greater Yellowstone Ecosystem (GYE) [45] and predicted that, given its greater landscape structural diversity, the GYE would be less sensitive and demonstrate fewer changes to bird communities as a result of exurban development than would the Adirondacks. Despite our predictions, we found similar responses to development among several avian guilds across these distinct regions.…”
Section: Introductionmentioning
confidence: 99%